2019
DOI: 10.1155/2019/2893041
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics and Faecal Metabolomics Integrative Analysis towards the Impaired Glucose Regulation and Type 2 Diabetes in Uyghur-Related Omics

Abstract: Objective Gut microbiota and their metabolites play an important role in the development of type 2 diabetes mellitus (T2DM). This research was designed to study the relationship between gut microbiota and faecal metabolites of Uyghur newly onset T2DM and impaired glucose regulation (IGR) patients. Materials and Methods A total of 60 different glycemic Uyghur subjects were enrolled and divided into T2DM, IGR, and normal glucose tolerance (NGT) groups. Metagenomics and LC-MS-based untargeted faecal metabolomics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
4
14
1
Order By: Relevance
“…Moreover, differences in β -diversity (PLS-DA) were observed in the three groups. Our results were consistent with those of previous studies, which reported that lower α -diversity indices (Shannon and Chao) of gut microbiota and different β -diversity were observed in T2DM patients compared with non-diabetic individuals ( Nuli et al., 2019 ; Zhao et al., 2019 ; Reitmeier et al., 2020 ). Therefore, we postulate that the onset and progression of diabetes and its retinal complications are related to alterations in the gut microbiota.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, differences in β -diversity (PLS-DA) were observed in the three groups. Our results were consistent with those of previous studies, which reported that lower α -diversity indices (Shannon and Chao) of gut microbiota and different β -diversity were observed in T2DM patients compared with non-diabetic individuals ( Nuli et al., 2019 ; Zhao et al., 2019 ; Reitmeier et al., 2020 ). Therefore, we postulate that the onset and progression of diabetes and its retinal complications are related to alterations in the gut microbiota.…”
Section: Discussionsupporting
confidence: 93%
“…However, Fusobacteria were highly abundant in the control group and Actinobacteria were highly abundant in SARS-CoV-2 diabetic group (Figure s4). The dominance of Firmicutes in diabetic patients were also described in other studies 27, 28 .…”
Section: Discussionsupporting
confidence: 75%
“…Gene variants or polymorphisms of IL1B and ENP1 have been found to correlate with T2DM in many human studies [ 39 41 ]. Moreover, starch and sucrose metabolism and MAPK signaling pathways have been implicated in the development of T2DM in multiple animal models and human studies [ 42 , 43 ]. The findings of the present study suggested that lnc-HIST1H2AG-6 and lnc-AIM1-3 play an important role in T2DM; thus, further investigation should be performed.…”
Section: Discussionmentioning
confidence: 99%